Investigating cryoprotectant effects on saccharomyces boulardii as probiotic strain during freeze-drying for tablet development - Mohd Akmal, Azhar (World Researchers Associations, 2025)
Freeze-drying is an effective method to maintain the therapeutic properties of probiotics in a tablet form by solidifying and then sublimating frozen water in the culture to increase their shelf life and stability. However, this method can also damage probiotic cells and can impact their viability. Cryoprotectants can improve the strain preservation of probiotics during drying, yielding a more superior and potent final product, but their efficacy depends on the microorganisms, cryoprotectant types and freeze-drying conditions. The present study looked at how different cryoprotectants affected a chosen probiotic strain Saccharomyces boulardii on its ability to survive after being freeze-dried for tablet manufacture. The yeast strain was harvested, mixed with cryoprotectants of different concentrations (sorbitol, lactose, sucrose and skim milk) and freeze-dried using a vacuum freeze dryer. After the powder was rehydrated, a plate dilution method was conducted to determine the number of viable cells. The results showed that using a cryoprotectant agent during freeze-drying significantly improved the survival rate by up to 40% compared to the control (3.65%).